THE LIFE CYCLE OF THE LAYOUTS OF FLEXIBLE AND RECONFIGURABLE MANUFACTURING AREAS AND LINES - Molnár, Zsolt; Tamás, Péter; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2021)
Nowadays, the life cycle of products has been significantly shortened. This trend is particularly noticeable in the electronics, automotive and food/beverage industries, where new product launches can occur monthly. The introduction of new products is often accompanied by changes in production processes, which also has a direct impact on the production layout. The life cycle of a production line and thus of a production arrangement can be much longer than the life cycle of the product, for which the production line was originally designed. The field of research on layout redesign demands posed by flexible manufacturing systems is novel and currently has very little literature.